Elaboración de un microencapsulado del extracto de tzinzo (tagetes minuta) mediante el método de secado por aspersión - Rodríguez Andachi, Evelin Abigail (2022)
The objective of this research was to elaborate a microencapsulated extract of Tzinzo (Tagetes minuta) through the spray drying method, using gum arabic and maltodextrin as encapsulating material. For the design and processing of the information, the Design Expert 8.0.6 program was used. Through an optimal IV response surface design, 13 experimental runs were carried out, the control factors being the air inlet temperature (ART) from 130 to 150 ºC and the feed flow rate (VFA) from 500 ml/h to 700 ml/h. The data obtained in the numerical optimization process showed the optimal conditions at 150°C and 500 ml/h, where a yield of 91.9%, 89.2% efficiency and 2.11% humidity were obtained. In addition, the optimal run was characterized, obtaining values of pH 5.3, apparent density 0.0254g/ml, compact density 0.0489 g/ml, titratable acidity 0.18% m/m citric acid, antioxidant capacity reducing iron 829.89 (µM Fe2+/g sample), Carr index 15.724, Hausner index 0.3889, angle of repose 33.27, hygroscopicity 8.824%, and solubility 22.47%, microscopy with a particle size of 6, 71 to 100 µm, they did not present cracks or apparent fissures, the microencapsulated has a high antioxidant capacity thus allowing the formation of an optimal powder.